The Outcome of Antibiotic Overuse before and during the COVID-19 Pandemic in a Tertiary Care Hospital in Oman - Nenad Pandak; Hilal Al Sidairi; Ibrahim Al-Zakwani; Zakariya Al Balushi; Shabnam Chhetri; Muna Ba'Omar; Sultan Al Lawati; Seif S. Al-Abri; Faryal Khamis (MDPI AG, 2023)
Antimicrobial resistance (AMR), a serious global public health challenge, may have accelerated development during the COVID-19 pandemic because antibiotics were prescribed for COVID-19. This study aimed to assess antibiotics use before and during the pandemic and correlate the results with the rate of resistant microorganisms detected in hospitalized patients during the study period. This single-center study looked retrospectively at four years of data (2018-2021) from Royal Hospital, Muscat, which is the biggest hospital in Oman with approximately 60,000 hospital admissions yearly. The consumption rate of ceftriaxone, piperacillin tazobactam, meropenem, and vancomycin was presented as the antibiotic consumption index, the ratio of defined daily dose (DDD) per 100 bed days. Analyses were performed using the nonparametric test for trend across the study period. Correlation between antibiotic consumption indexes and the isolated microorganisms in the four-year study period was performed using Spearman's rank correlation coefficient. We compared data from the pre-COVID-19 to the COVID-19 period. Though more patients were admitted pre-COVID-19 (132,828 versus 119,191 during COVID-19), more antibiotics were consumed during the pandemic (7350 versus 7915); vancomycin and ceftriaxone had higher consumption during than before the pandemic (p-values 0.001 and 0.036, respectively). Vancomycin-resistant Enterococcus (VRE) and Candida auris were detected more during the COVID-19 period with p-values of 0.026 and 0.004, respectively. Carbapenem-resistant Enterobacterales (CRE), vancomycin-resistant Enterococcus spp., and C. auris were detected more often during the pandemic with p-values of 0.011, 0.002, and 0.03, respectively. Significant positive correlations between antibiotic consumption and drug-resistant isolates were noted. This study confirms that the overuse of antibiotics triggers the development of bacterial resistance; our results emphasize the importance of antibiotic control.